Potential of Foliar Fertilizer and Organic Additives for Vanda tricolor Protocorm Regeneration - Siti Yulaekhah; Maria Marina Herawati; Endang Pudjihartati (The University of Lampung, 2025)
Vanda tricolor orchid is propagated by in vitro culture using Vacin & Went (VW) media. The price of this media is quite high, so research is needed on alternative media that can replace VW media. The objectives of this study were to (1) determine the effect of foliar fertilizer concentration and addition of organic materials on in vitro protocorm regeneration in to planlets, (2) obtain a combination of foliar fertilizer concentration and organic materials that can be used to subtitude VW as a medium for Vanda tricolor protocorm regeneration. The treatments tested were the concentration of NPK foliar fertilizer (21:21:21), namely: 1 g/L, 1.5 g/L, 2 g/L, and 2.5 g/L and various organic materials, namely: no organic material, banana, potato, banana+potato. VW was use as a control. Data analysis to compare VW control with all treatments used Orthogonal Contrast further test, while to compare between treatment combinations using Analysis of Variance (ANOVA) and DMRT further test at the 5% level. The results showed that leaf fertilizer at a concentration of 2.5 g/L was able to accelerate the formation of shoots and roots without the addition of organic material. In addition, leaf fertilizer media plus potatoes can be used to replace VW as a protocorm regeneration media at affordable cost.